A bipolar comparison of deep ice cores from Antarctica (Dome Fuji) and Greenland (GRIP) (scientific paper) - Shoji, Hitoshi; Miyamoto, Atsushi; Shimohara, Kimiko; Watanabe, Okitsugu; Fujii, Yoshiyuki; Kamiyama, Kokichi; Motoyama, Hideaki; Goto-Azuma, Kumiko; Igarashi, Makoto; Takata, Morimasa; Kohno, Mika; Fujita, Shuji; et al. (2003)
P(論文) Oxgen isotope ratio and chemistry profiles were compared to find the corresponding interstadials during the Wisconsin Ice Age between the GRIP (Greenland) and Dome Fuji (Antarctica) deep ice core data for the past one hundred and sixty thousand years. Eight interstadials in GRIPδ18O profile were found to correspond to those in Dome Fuji δ18O profile. Eleven interstadials in GRIPδ18O profile were found to correspond to those in Dome Fuji chemistry (calcium, nitrate and sulfate) profile, which is better suited for the purpose of interstadial search than the δ18O profile at Dome Fuji. The Eemian interglacial period at Dome Fuji seems to be much shorter and more stable than that in the GRIP profile. Three major periods having higher contents of calcium, nitrate and sulfate appear at Dome Fuji, ranging (1) between interstadials number 1 and 8, (2) between interstadials number 17 and 19, and (3) before the Eemian, which correspond to relatively cold and stable periods in the GRIP δ18O profile. These findings promise a favorable outcome from more detailed bipolar comparison in the future for an understanding of climatic linkage conditions and the driving forces between northern and southern hemispheres. departmental bulletin paper